2011
DOI: 10.1017/s1751731110002685
|View full text |Cite
|
Sign up to set email alerts
|

Podolian beef production on pasture and in confinement

Abstract: the effect of rearing system (confined (C) v. free ranging (FR)) and season (spring v. summer) was evaluated on behaviour, immune and blood parameters and beef production (experiment 1). From February to August 2008, the effect of rearing system was only evaluated on beef production (experiment 2). A total of 12 Podolian young bulls were used each year. They were slaughtered at 18 and 15 months of age in 2007 and 2008, respectively. Herbage mass and pasture composition were monitored during the 2 years. Pastur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
5
18
1
3
Order By: Relevance
“…During a 6-h period, the behaviour of a focal animal, chosen at random before the start of an observation session, was continuously monitored. They were habituated to the presence of humans following a familiarisation procedure (Braghieri et al, 2011). For practical reasons, all observations were performed during daylight.…”
Section: Pasture Composition and In Vivo Digestibilitymentioning
confidence: 99%
“…During a 6-h period, the behaviour of a focal animal, chosen at random before the start of an observation session, was continuously monitored. They were habituated to the presence of humans following a familiarisation procedure (Braghieri et al, 2011). For practical reasons, all observations were performed during daylight.…”
Section: Pasture Composition and In Vivo Digestibilitymentioning
confidence: 99%
“…However, previous studies have reported satisfactory performances approaching 1 kg average daily gain (ADG) with only grass and sometimes with minimal amount of concentrate in tropical and Mediterranean settings (Esterhuizen et al, 2008;Braghieri et al, 2011). Current farming systems must balance agro-ecological services and enhancement of biodiversity while reducing inputs and controlling output of greenhouse gases to be truly multifunctional.…”
Section: Introductionmentioning
confidence: 99%
“…Their most common rearing system is based on either no-shelter pasture or pasture with nocturnal shelter . Most often, cows and calves are not supplemented, whereas young adults receive concentrates in the finishing period (Braghieri et al 2011a(Braghieri et al , 2013. According to Liu et al (2010), ecosystem services include all the benefits that people obtain from ecosystems and they are divided (Millennium Ecosystem Assessment 2005) into four categories: provisioning services (e.g.…”
Section: The Multifunctional Role Of Podolian Farming Systemmentioning
confidence: 99%